Spatial Analysis of Seismic Hazard based on Dynamical Characteristics of Soil in Kota Baru, South Lampung - V. L. Ipmawan; I. N. P. Permanasari; R. N. Siregar (Journal of Science and Applicative Technology, 2019)
Kota Baru, a new capital Lampung province location, planned and developed since 2012, will be a densely populated in near time. The province located in near Semangko fault, southern of Sumatra Island, is a vulnerable area to earthquake. Seismometer was deployed for 15 points in Kota Baru for recording mictrotremor. The signal was analyzed by HVSR method produced fundamental frequency f0, amplitude A0, and seismic vulnerability index Kg. The range of frequency value is about 0.56 Hz to 1.46 Hz. The range of amplitude value is about 2.3 to 6.17. There is linear relation between Kg and the damage caused by earthquake. The Kota Baru classification of seismic hazard map was generated by plotting the value of Kg. The area at the northeast of Kota Baru is more risky to be inhabited because it has higher value of Kg. The more safety area located in near T7 and T15 because it has lower value of Kg than theothers.